2014
DOI: 10.3945/jn.113.182501
|View full text |Cite
|
Sign up to set email alerts
|

Wax Esters from the Marine Copepod Calanus finmarchicus Reduce Diet-Induced Obesity and Obesity-Related Metabolic Disorders in Mice

Abstract: We showed previously that dietary supplementation with oil from the marine zooplankton Calanus finmarchicus (Calanus oil) attenuates obesity, inflammation, and glucose intolerance in mice. More than 80% of Calanus oil consists of wax esters, i.e., long-chain fatty alcohols linked to long-chain fatty acids. In the present study, we compared the metabolic effects of Calanus oil-derived wax esters (WE) with those of purified eicosapentaenoic acid (EPA) + docosahexaenoic acid (DHA) ethyl esters (E/D) in a mouse mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 49 publications
5
29
2
Order By: Relevance
“…Table 2 reports new drugs and drug derivatives obtained by different marine organisms proposed in anti-obesity treatment [62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90,91,92,93,94]. …”
Section: Treatment Of Obesitymentioning
confidence: 99%
“…Table 2 reports new drugs and drug derivatives obtained by different marine organisms proposed in anti-obesity treatment [62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90,91,92,93,94]. …”
Section: Treatment Of Obesitymentioning
confidence: 99%
“…Calanus finmarchicus is the most abundant herbivorous zooplankton that that are enriched in both n-3 PUFA and LCMUFA [38]. Several studies showed beneficial effect of dietary Calanus oil in CVD risk, such as reducing atherosclerotic plaque formation, abdominal fat accumulation and hepatic steatosis, and improving glucose tolerance in mice through multiple mechanisms, including regulation of inflammatory response-associated gene expression in livers and adipose tissues [3941]. Nevertheless, because these marine oils also contain considerable amounts of n-3 PUFA and intake of these marine oils increased plasma and organ levels of EPA and DHA, one cannot exclude the possibility that the benefit from this diet was only due to n-3 PUFA consumption.…”
Section: Animal Studiesmentioning
confidence: 99%
“…Analysis of Calanus Oil have shown that levels of heavy metals and organic pollutants are well below the limits specified for marine oils by the Commission Regulation (EC) No1881/2006 and 629/2008 (Commission of the European Communities) (manuscript in preparation). Recent studies suggest that inclusion of low levels of Calanus oil or isolated wax esters in feed to rodents on a Western type high fat diet (HFD), may reduce atherogenesis and have other positive health effects such as reduced abdominal obesity, reduced adipose tissue inflammation and improvement in systemic glucose tolerance .…”
Section: Introductionmentioning
confidence: 99%